IMPROVING THE WORK ABILITY OF INVESTIGATORS IN DRUG ERADICATION - Widiastono, Wahyu; Sudardi, Sudardi; Mansur, Mansur (Universitas Brawijaya, Indonesia, 2019)
As a law enforcement institution within the Indonesian Navy, Indonesian Naval Military Police (Pomal) has the authority to handle all types of military criminal offences, general criminal offences, and disciplinary violations committed by the Indonesian Navy. One of the criminal offenses committed by the Indonesian Navy which is the concern of the Chief of Staff of Indonesian Navy is drug abuse. The purpose of this study is to analyse what factors influence the work ability of Indonesian Naval Military Police Center (Puspomal) investigators and to analyse how to improve the work ability of Puspomal investigators for drug eradication operations within the Indonesian Navy. This study uses a qualitative method. Based on data analysis in this study, it can be concluded that the work ability of Puspomal investigators is influenced by motivation, knowledge, skills, facilities and infrastructure, organisation, and investigation budget. Recommendations in this study Puspomal investigators in carrying out drug eradication operations within the Indonesian Navy can be given rewards in accordance with applicable legal procedures when succeeding in uncovering the crime of drug eradication to motivate and improve the work ability of Puspomal investigators.